Osumilite–melt interactions in ultrahigh temperature granulites: Phase equilibria modelling and implications for the P–T–t evolution of the Eastern Ghats Province, India - Korhonen, Fawna; Brown, M.; Clark, Christopher; Bhattacharya, S. (Wiley - Blackwell, 2013)
The exposed residual crust in the Eastern Ghats Province records ultrahigh temperature (UHT) metamorphic conditions involving extensive crustal anatexis and melt loss. However, there is disagreement about the tectonic evolution of this late Mesoproterozoic–early Neoproterozoic orogen due to conflicting petrological, structural and geochronological interpretations. One of the petrological disputes in residual high Mg–Al granulites concerns the origin of fine-grained mineral intergrowths comprising cordierite + K-feldspar ± quartz ± biotite ± sillimanite ± plagioclase. These intergrowths wrap around porphyroblast phases and are interpreted to have formed by the breakdown of primary osumilite in the presence of melt trapped in the equilibration volume by the melt percolation threshold. The pressure (P)–temperature (T) evolution of four samples from three localities across the central Eastern Ghats Province is constrained using phase equilibria modelling in the chemical system Na2O–CaO–K2O–FeO–MgO–Al2O3–SiO2–H2O–TiO2–Fe2O3 (NCKFMASHTO). Results of the modelling are integrated with published geochronological results for these samples to show that the central Eastern Ghats Province followed a common P–T–t history. This history is characterized by peak UHT metamorphic conditions of 945–955 °C and 7.8–8.2 kbar followed by a slight increase in pressure and close-to-isobaric cooling to the conditions of the elevated solidus at 940–900 °C and 8.5–8.3 kbar. In common with other localities from the Eastern Ghats Province, the early development of cordierite before osumilite and the peak to immediate post-peak retrograde reaction between osumilite and melt to produce the intergrowth features requires that the prograde evolution was one of contemporaneous increasing pressure with increasing temperature.This counter-clockwise (CCW) evolution is evaluated for one sample using inverse phase equilibria modelling along a schematic P–T path of 150 °C kbar−1 starting from the low P–T end of the prograde P–T path as constrained by the phase equilibria modelling. The inverse modelling is executed by step-wise down temperature reintegration of sufficient melt into the residual bulk chemical composition at the P–T point of the 1 mol.% melt isopleth at each step, representing the melt remaining on grain boundaries after each prograde drainage event, to reach the melt connectivity transition (MCT) of 7 mol.%. The procedure is repeated until a plausible protolith composition is recovered. The result demonstrates that clastic sedimentary rocks that followed a CCW P–T evolution could have produced the observed mineral assemblages and microstructures preserved in the central Eastern Ghats Province. This study also highlights the role of melt during UHT metamorphism, particularly its importance to both chemical and physical processes along the prograde and retrograde segments of the P–T path. These processes include: (i) an increase in diffusive length scales during the late prograde to peak evolution, creating equilibration volumes larger than a standard thin section; (ii) the development of retrograde mineral assemblages, which is facilitated if some melt is retained post-peak; (iii) the presence of melt as a weakening mechanism and the advection of heat by melt, allowing the crust to thicken; and (iv) the effect of melt loss, which makes the deep crust both denser and stronger, and reduces heat production at depth, limiting crustal thickening and facilitating the transition to close-to-isobaric cooling.